Gestures of Conciliation - Mitchell, Christopher. author. aut Link
XVIII, 333 p.
Keywords: Gestures of Conciliation examines the ideas, assumptions and theories that underpin how leaders of parties in intractable conflicts begin and sustain a process of peacemaking by offering to their adversaries 'olive-branches' - in more modern terms symbolic gestures, concessions, tension-reducing moves or confidence-building measures. It discusses means of overcoming political and psychological barriers to accurate communication, trust-building, domestic consensus formation, and 'ripe' conditions for conciliation, suggesting practical guidelines for accommodation.